Angelina Ballerina loves the library - Holabird, Katharine; Craig, Helen (Holabird, Katharine. Angelina Ballerina., 2021)
Angelina Ballerina is excited to go to the library and get a library card. When she finds out she can only check out five books at a time, she comes up with a plan.